HUBUNGAN PSYCHOLOGICAL WELL-BEING DENGAN KINERJA GURU TK DI KECAMATAN TAMBANG KABUPATEN KAMPAR - Jumi Yanti; Ria Novianti; Rita Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The aim of this research is to know whether there is correlation between psychological well-being with the performance of kindergarten teachers in the Tambang District of Kampar Regency. The population in this study were kindergarten teachers in the Tambang District of Kampar Regency with 64 teachers, this sample was used by 44 teachers who were taken using saturated sample techniques. The method used is Pearson Product Moment correlation to see the relationship between psychological well-being variables and teacher performance. The technique of data collection used is koesioner in the form of a Likert scale. Data analysis techniques use scale trials and statistical method analysis with the SPSS program for Windows Ver. 17. Based on the results of hypothesis testing obtained there is a positive and significant relationship between psychological well-being and the performance of kindergarten teachers in the Tambang District of Kampar Regency. This can be seen from the correlation coefficient of rxy = 0.518 and a significant level of 0,000 <0.05. The level of the relationship between psychological well-being and teacher performance is included in the medium category with a determinant coefficient value of 26.8%, meaning that teachers of psychological well-being have an influence of 26.8% on teacher performance.Keywords: Psychological Well Being, Teacher Performance